Habitat of the amphibious mudskipper Periophtalmodon schlosseri in Songkhla Lake, Thailand - MANASAWAN SAENGSAKDA PATTARATUMRONG; THANIDA POMPHA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pattaratumrong MS, Pompha T. 2024. Habitat of the amphibious mudskipper Periophtalmodon schlosseri in Songkhla Lake, Thailand. Biodiversitas 25: 1875-1881. This study aimed to investigate the preferred habitat of giant mudskippers, Periophtalmodon schlosseri Pallas 1770. It was conducted from August to October 2022 at six sampling stations in Koh Yoh, a small island in the Lower Songkhla Lake. Environmental parameters such as organic matter and organic carbon in sediment, temperature, salinity, dissolved oxygen, and substrate were observed. The results indicate that the density of giant mudskipper weak to moderate correlates with all studied environmental parameters (P<0.05). Within the study area, the highest population density of P. schlosseri was recorded in the mudflat habitat adjacent to mangroves, and the lowest density was recorded in the mudflat habitat with a seawall, absent with nearby mangroves. This study suggests that environmental conditions affect the abundance of giant mudskippers, but this does not reach the limiting threshold; the more influential factor for this species is the character of the habitat. The mangrove habitat should be conserved and protected from development and urbanization. These results provide insights into the preferred habitat and offer a better understanding of the ecology of these fishes in the estuarine lake.